2018
DOI: 10.1093/bioinformatics/bty790
|View full text |Cite
|
Sign up to set email alerts
|

smCounter2: an accurate low-frequency variant caller for targeted sequencing data with unique molecular identifiers

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 30 publications
0
75
0
Order By: Relevance
“…The smCounter2 pipeline, specially designed for the accurate calling of low‐frequency variants from QIAseq‐based targeted sequencing data, was employed for data processing and variant calling. UMI tags enabled error correction for most of the sequencing and PCR errors, and a refining algorithm was used to further amend those errors that were not correctable with UMI.…”
Section: Methodsmentioning
confidence: 99%
“…The smCounter2 pipeline, specially designed for the accurate calling of low‐frequency variants from QIAseq‐based targeted sequencing data, was employed for data processing and variant calling. UMI tags enabled error correction for most of the sequencing and PCR errors, and a refining algorithm was used to further amend those errors that were not correctable with UMI.…”
Section: Methodsmentioning
confidence: 99%
“…We sequenced reference material NA12878 in the 11 panels using the standard QIAseq targeted DNA workflow on Illumina platforms. The reads were processed by the GeneGlobe QIAseq DNA data analysis pipeline [12]. After BWA-MEM mapping (GRCh37/hg19), we grouped reads from each primer by the 5' mapping location (or binding site) and counted the number of unique molecular identifiers (UMI) that were attached during library preparation (Fig.…”
Section: Data Preparationmentioning
confidence: 99%
“…Another UMI-based dataset used for our evaluation is the physical mixture (mixed at 1:99 ratio) of the reference materials NA12878 and NA24385 which are both well-characterized for germline polymorphisms 45 . Xu et al 45 have shown that smCounter2 outperformed all other applicable methods on this dataset. Therefore, we compared UVC with only smCounter2.…”
Section: Performance Comparison On Tumor-only Sequencing Datasets Witmentioning
confidence: 99%
“…Meanwhile, UVC was not aware of any such error profiles before running with its default parameters. Figure 2 shows that UVC outperformed smCounter2 for calling SNVs and InDels, even though smCounter2 was enhanced with UMI-specific repetitive region filters 45 . Notably, without the hard filter by EROR, UVC would generate approximately 10 times more false positive SNV calls, even though the hard filter by EROR rejects approximately 10% true positive SNV calls (Fig.…”
Section: Performance Comparison On Tumor-only Sequencing Datasets Witmentioning
confidence: 99%
See 1 more Smart Citation